Recycling of sewage sludge as production medium for cellulase by a Bacillus megaterium strain - Adel Ali Saeed Al-Gheethi (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Background Cellulase is one of the enzymes commonly used in several agricultural, industrial and sewage sludge treatment processes. The present study aimed to investigate the potential use sludge generated from sewage treatment plants as a production medium for cellulase by B. megaterium strain that was isolated from a sewage treatment plant. The production of cellulase in the sludge medium was compared to different cellulosic materials: cotton, filter paper, bagasse and sawdust as well as to galactose, fructose, lactose, maltose, mannitol, mannose, ribose, sucrose and xylose. The production of cellulase was conducted at optimum conditions (0.4 mL of the bacterial inoculum, 45 C, 72 h, pH 6.5 and citrate phosphate buffer) that were determined in this study. Results The sludge medium has induced the cellulase production by B. megaterium strain compared to cotton, filter paper, bagasse and sawdust. However, B. megaterium produced high cellulase in the presence of carbohydrate compounds as carbon source. More cellulase was produced in the sludge medium containing low concentrations of Ni2?, Zn2? and Cu2? ions. Discussion The ability of B. megaterium strain to produce cellulase in the sewage sludge medium was due to that the strain has acclimatized to resist heavy metals and produce the enzyme genetically. Moreover, B. megaterium has an important environmental role for reuse of sewage sludge as production medium for cellulase that could be used in many of applications, including production of animal feed, formulation of detergents, juice clarification, paper industry and wine production.